2022
DOI: 10.1063/5.0111025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of superhydrophobic area occupancy and impact angle on the water entry dynamics of spheres

Abstract: In this work we reported a kind of deflecting air cavity generation strategy through controlling the superhydrophobic (SHB) area occupancy and the impact angle of water entry. The influence of SHB area occupancy and impact angle on the water entry dynamics and drag reduction characteristics of spheres are also explored through both experimental and theoretical analysis. For a hemispherically-coated sphere, it is found that the formed air cavity would reach a maximum deflecting angle when the impact angle of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It has been shown that corona splash depends on the dynamics of the escaping air beneath the extended sheet. [ 35,36,50 ] The interactions of compressed gas between the liquid sheet and microstructured surfaces are a key determinant of droplet instability in prompt splashing and corona splashing. The discrete micropillars are sufficient to wettability the liquid sheet into the spaces between the solid structures for positively skewed surfaces and it flows along the channel consisting of discrete micropillars.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that corona splash depends on the dynamics of the escaping air beneath the extended sheet. [ 35,36,50 ] The interactions of compressed gas between the liquid sheet and microstructured surfaces are a key determinant of droplet instability in prompt splashing and corona splashing. The discrete micropillars are sufficient to wettability the liquid sheet into the spaces between the solid structures for positively skewed surfaces and it flows along the channel consisting of discrete micropillars.…”
Section: Resultsmentioning
confidence: 99%
“…Superhydrophobic (SHB) surfaces with excellent water repellency and self-cleaning ability are widely attractive in drag reduction, energy saving, stain resistance for wearable clothing, microfluidics, and biomedicine fields. , However, it is still a challenge to achieve continuous and durable anti-liquid ability on the SHB surfaces because of their poor mechanical properties and resistance to wear . Under the external pressure and contact load, the prepared multi-scale micro/nano-structures would be easily removed during the friction process, and the SHB coating would also be destroyed because of low adhesion to the base .…”
Section: Introductionmentioning
confidence: 99%